Biology and Management of Wheat Pathogens - Dr. K.D. Srivastava - IPS, Editor (Indian Phytopathology, 2012)
Biology and Management of Wheat Pathogens by Dr.Â K.D. Srivastava, Studium Press (India) Pvt. Ltd., Daryaganj, New Delhi, 284 p., 2010, Price Rs. 995.00